Through the Justice and the Sovereignty Over Natural Resources: An Analysis of 100 % Foreign Direct Investor Ownership over Geothermal Sector Project - Dinda Silviana Putri; Haikal Arsalan; Cecillia Yudo; Stefani Siauwanda (Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2024)
The enactment of the Job Creation Law and the Presidential Decree Number 10 of 2021 concerning the Investment Business Sector has make it possible for foreign investors to gain 100% ownership over geothermal sector projects. This policy then raises an important question, which is whether such policy violates the Sovereignty over Natural Resources doctrine, and if so, what kind of policy should be made. This study aims to analyze Indonesia’s geothermal foreign direct investment policy through the Sovereignty over Natural Resources doctrine and implementation of the fair efficiency principle, which also includes aspects of efficiency and justice. This study is normative legal research using statute approach and conceptual approach. The result of this study indicates that, although 100% foreign investor ownership over geothermal exploitation projects could be seen as an efficient policy to attract investors. However, it is still lacking the proper regulation to ensure said policy will not cause harm to the people.